HISTORY OF THE ACTIVITIES OF AGRICULTURAL EXPERIMENTAL STATIONS IN TURKISTAN (EARLY 20TH CENTURY) - Narziyeva Maftuna Adxamovna (Web of Journals Publishing, 2025)
This article provides reflections on the activities of agricultural experimental fields operating in the Turkestan region during the period of the Russian Empire.
Keywords: Experimental field, greenhouse, vegetable, orchard, fruit seedling, bed, beekeeping, productivity, shabdar, tomato, cotton farming, English bed, French bed, new techniques, labor tools.